Delirium in advanced disease. Issue 982 (3rd August 2007) - Harris, Dylan
Abstract : Delirium in advanced disease, while common, is often not recognised or poorly treated. The aim of management of delirium is to assess and treat reversible causes in combination with environmental, psychological and pharmacological intervention to control symptoms. Delirium presents significant distress and impedes communication between patients and their families at the end of life. A structured approach to recognise, assess and manage delirium is essential for all clinicians caring for patients with terminal illness.